Living conditions and public health status in three urban slums of Lagos, Nigeria (South East Asia Journal of Public Health, 2014)
Lagos metropolis, southwestern Nigeria, is faced with environmental problems ranging from slums and informal settlements, to crime and delinquency. The aim of the study was to explore the demographic characteristics, migra-tion history and living conditions of 2,434 residents of Ajegunle, Ijora Oloye and Makoko in Lagos metropolis. A cross-sectional survey was conducted between June 2010 and October 2012 using a semi-structured questionnaire. Units of analysis used were households. Many of the respondents are low-income earners working in the informal service sectors, and living in unhygienic conditions. The communities are densely populated, with more than five people living in a room. Residents make use of poor and overstressed facilities and inadequate water and electricity supplies. They also lack appropriate garbage disposal facilities and good drainage. Personal hygiene habits are very poor; open defecation in ditches and the lagoon is widely practiced. Respondents are faced with perennial flooding due to blocked drainage systems resulting in a number of diseases, such as malaria, diarrhea, cold and cough. Migra-tion has led to uncontrolled and unplanned developments of slums in metropolitan Lagos. This in turn has led to poverty, unemployment, illiteracy, polluted environment, uncontrolled population growth and health problems in the slums as are observed in this study. There is an urgent need for comprehensive interventions from the government and other organizations to strengthen existing programs to improve the health and quality of life of this vulnerable population. South East Asia Journal of Public Health 2013; 3(1): 36-41 DOI: http://dx.doi.org/10.3329/seajph.v3i1.17709